Superior potassium-ion storage properties by engineering pseudocapacitive sulfur/nitrogen-containing species within three-dimensional flower-like hard carbon architectures. (May 2020) - Li, Wenda; Wang, Dezhu; Gong, Zhijiang; Guo, Xiaosong; Liu, Jing; Zhang, Zhonghua; Li, Guicun
Abstract: Rechargeable non-aqueous potassium-ion batteries have been regarded as one of ideal candidates for large-scale electric energy storage applications. However, the achievement of high reversible capacity and rate capability is still a great challenge. In this work, an extraordinary S-/N-/O- multielement-doped three-dimensional (3D) flower-like hard carbon architecture is firstly proposed as promising anode material for low-cost potassium-ion batteries. The 3D flower-like architecture not only provides abundant exposed surface-active sites but acts as highly conductive interconnected network for electron transport. More encouragingly, the introduction of highly reactive -N-C x -S- species has been revealed to show highly reversible pseudo-capacitive charge storage behavior, inherently enlarging the slope reversible capacity to the highest value of 423 mAh g −1 at low current density of 0.05 A g −1 . As well, benefitted from the structural and compositional advantages, an unprecedented rate capability (251 mAh g −1 at 1.0 A g −1 ) and stable cycling stability (362 mAh g −1 after 300 cycles at 0.5 A g −1 ) has been obtained, which outperforms most of carbonaceous materials for K-ion storage. Our present work not only provide new understandings on surface/conversion-synergistic driven K-ion storage mechanisms but offer effective material engineering strategies for improving the properties of potassium-ion batteries. Graphical abstract: Image 1 Highlights: S-/N-/O- multielement-codoped engineering strategy was applied firstly. Flower-like hard carbon architectures possess abundant surface-active sites. Highly reactive -N-C x -S- species showed highly reversible pseudo-capacitive behavior. The surface/conversion-synergistic driven K-ion storage mechanism was proposed.